Thermal transport in porous composite phase change materials - Zhang, Shuai (2023)
Inorganic salts are widely used medium- and high-temperature phase change materials (PCM). However, their thermal conductivity is low, and since salts are highly corrosive, many conventional heat transfer enhancement methods do not apply. In this research, the ceramic foam was used to enhance the heat transfer of salts. The ceramic foam is open-cell, and its pore size is large (~mm), which enables the natural convection of PCM and benefits thermal transport. And it is fabricated alone and is integrated with molten salt easily; hence, the foam and salt can be maintained separately (rather than the whole CPCM), and the maintenance cost is reduced. This research covers property measurement, material preparation, compatibility test, and performance analysis. The thermo-physical properties of nitrate salts with various component fractions were measured. Mixing nitrate salts can decrease the melting point without impairing the latent heat; a molecular dynamics simulation was performed to provide microscopic insights. The ceramic foam/salt composite phase change material (CPCM) with excellent compatibility was fabricated; the thermal transport in the porous CPCM was studied experimentally and numerically. The melting front is significantly curved, indicating natural convection is strong, which is attributed to the low viscosity of salts. The melting rate of the CPCM with a pore density of 10 PPI (Pores Per Inch) is increased by 51.5%, and the porosity has a more significant effect than pore density on the melting performance. For the shell-and-tube heat storage unit, the ceramic foam with varying outer diameters is optimal in melting rate, total stored energy, and energy storage rate. The thermal performance under solar fluctuation is also studied; strong solar radiation not only improves the energy storage rate but also increases the total stored energy; compared to pure PCM, ceramic foam/salt CPCM is more sensitive to solar fluctuation.